Exploring gender differences in online metacognitive reading strategy use among ESL university students during academic reading / Noor Azua Mohd Putera @ Bahatera - Mohd Putera @ Bahatera, Noor Azua (Faculty of Education, 2011)
This study explores the gender differences III online metacognitive reading strategy use among ESL university students while reading academic texts. The sample consisted of 80 male and 80 female Semester Two Diploma in Communication and Media Studies students, from the Faculty of Communication and Media Studies in UiTM Alor Gajah. Firstly, this study investigates the online metacognitive reading strategies used by male and female students in UiTM Alor Gajah while reading academic texts in terms of types and frequency. Secondly, it examines the differences in the use of online metacognitive reading strategies between male and female in terms of types and frequency. This research study is a non-experimental cross sectional survey design. The independent variable is the gender of the participants and the dependent variable is the metacognitive awareness as measured by the Online Survey of Reading Strategies (OSORS) developed by Neil J. Anderson (2003) which comprised three sub-categories, namely global reading strategies (18 items), problem-solving strategies (11 items), and support strategies (9 items). The research questions were examined using quantitative data analysis which includes the descriptive statistics (Means and Standard Deviations) and the inferential statistics namely one-way repeated measures (within subjects) ANOVA, the Post-Hoc Bonferroni Adjusted Pairwise Comparison of Means test, as well as the Independent Samples T-tests. The findings indicated that male and female students use all the problem-solving strategies with high frequency and all the global and support strategies with moderate frequency. Male students used problem-solving strategies with the highest frequency followed by global strategies and then support strategies, while female students used problem-solving strategies with the highest frequency followed by both global strategies and support strategies with similar frequency. Next, there were no statistically significant differences in the frequency of use of the overall, global, problemsolving and support strategies between male and female students. However, among the 38 individual strategies used, male students used 2 strategies with significantly higher frequency than female students which are problem-solving and global strategies. Female students used only I individual strategy with significantly higher frequency than male students which is a support strategy. This study also discusses the pedagogical implications, limitations, and suggestions for future study.